Experimental adjustment and validation of a generalized solar‐assisted cogeneration system model. (29th May 2019) - Hovsapian, Rob; Dias, Fernando G.; Vargas, Jose V.C.; Sensoy, Tugba S.; Ordonez, Juan C.
Summary: A solar‐assisted absorption cooling and water heating system model is adjusted and experimentally validated in this study. Conservation laws are combined with available heat and mass transfer empirical correlations to quantify the diverse types of flows that cross the system. The model is generalized by nondimensionalizing the variables, and the resulting system of ordinary differential equations is solved for dimensionless temperatures with respect to time. Next, the model is experimentally adjusted through the solution of the inverse problem of parameter estimation, through which geometric, operating parameters and physical terms are identified and adjusted (or added) according to a first set of measured temperature data. The adjusted model is then validated using a second experimental data set, and the results are presented in normalized form for design, control, and optimization of similar systems. Abstract : A solar‐assisted absorption cooling and water heating system model is adjusted and experimentally validated in this study. The model is experimentally adjusted through the solution of the inverse problem of parameter estimation, through which geometric, operating parameters, and physical terms are adjusted according to a first set of measured temperature data. The adjusted model is then validated using a second experimental data set, and the results are presented in normalized form for design, control, and optimization of similar systems.